Violence against individuals with disabilities: a synthesis of studies on prevalence and risk. (7th October 2012) - Hughes, K; Jones, L; Wood, S; Bellis, MA
Abstract : Background: Around 15% of the world's population has a disability. Individuals with disabilities are frequently reported to be at increased risk of violence yet quantitative syntheses of studies on this issue are scarce. Aims: To quantify violence against individuals with disabilities through systematic review and meta-analyses. Methods: 12 electronic databases were searched to identify studies reporting prevalence of violence against individuals with disabilities, or their risk of violence compared with non-disabled individuals. Studies of children and adults were addressed separately, focusing on lifetime violence in children and past year violence in adults. Studies were quality assessed and data were pooled for analysis. Results: Of 10 663 references, 26 adult and 17 child studies were included. Most had been conducted in high income studies. In adults, pooled prevalence of violence in the past year was 3.2%, with a pooled crude OR of 1.5. Prevalence and odds were highest in those with mental health conditions, although insufficient studies were available for most disability types. For children, pooled prevalence of lifetime violence was 26.7%, with a pooled crude OR of 3.7. Violence was elevated in children with mental/intellectual disabilities; again insufficient studies were available for other disability types. Significance: Our review confirms that individuals with disabilities are at increased risk of being victims of violence. However, available studies have methodological weaknesses and gaps exist in the types of disability and violence they address. Further high quality studies are needed, particularly in low- and middle-income countries, to support worldwide preventive action.